2014
DOI: 10.1038/srep07578
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Massless Dirac Fermions in Non-topological Type Edge States

Abstract: There are two types of intrinsic surface states in solids. The first type is formed on the surface of topological insulators. Recently, transport of massless Dirac fermions in the band of “topological” states has been demonstrated. States of the second type were predicted by Tamm and Shockley long ago. They do not have a topological background and are therefore strongly dependent on the properties of the surface. We study the problem of the conductivity of Tamm-Shockley edge states through direct transport exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Periodic arrays of antidots have been studied as a way to open a band gap in graphene [56][57][58] or to obtain waveguiding effects [59,60]. Furthermore, a single perforation in a graphene sheet has been considered as a nanopore for DNA sensing [61,62] and recent studies in magnetic fields have shown the AharonovBohm effect appearing in conducting edge states around a nanohole [63].…”
Section: Vortex Currents Near Perforationsmentioning
confidence: 99%
“…Periodic arrays of antidots have been studied as a way to open a band gap in graphene [56][57][58] or to obtain waveguiding effects [59,60]. Furthermore, a single perforation in a graphene sheet has been considered as a nanopore for DNA sensing [61,62] and recent studies in magnetic fields have shown the AharonovBohm effect appearing in conducting edge states around a nanohole [63].…”
Section: Vortex Currents Near Perforationsmentioning
confidence: 99%
“…For the indirect interband photon emission to dominate over the "normal" Drude absorption, the long-wave length Fourier components of the scattering potential should prevail. Such kind of scattering potentials can be formed also by extended surface corrugations, quantum dots on the graphene bilayer surface [35], and nanohole arrays [36,37].…”
mentioning
confidence: 99%
“…It was found [16] that the spectrum of Tamm-Shockley edge states in graphene is linear with respect to momentum, which is similar to a section of the conical spectrum of SSs in TIs. Moreover, the band character of the conductivity through these states in normal conditions [17] was proved by a direct transport experiment. Let us describe a theory necessary to explain these experiments.…”
Section: Edge States In Graphenementioning
confidence: 99%
“…The wave function of edge states is exponentially localized near the boundary. A typical localization length determined from experiment [17] is 2 nm. The value of a should be determined from comparison with experiment; however, from a comparison with model microscopic calculations [66,67], one should expect that it is small: |a| ≪ 1.…”
Section: Edge States In Graphenementioning
confidence: 99%
See 1 more Smart Citation